Comparison of sublingual and vaginal misoprostol for second-trimester pregnancy terminations. - Forozan Milani; Seyede Hajar Sharami; Saeedeh Arjmandi (Tehran University of Medical Sciences, 2014)
Objective: Comparing sublingual and vaginal misoprostol in second trimester pregnancy termination. Materials and methods: In this study 268 women at 12-24 weeks of gestation candidate for pregnancy termination were enrolled. Women were randomly divided in two groups. The first group received 400 µg sublingual misoprostol and vaginal placebo and the second group received 400 µg vaginal misoprostol and sublingual placebo every 4 hours for a maximum of five doses. The course of misoprostol was repeated if the women did not abort within 24 hours. }Results: The median induction-to-abortion interval was shorter in sublingual group (12/72 hours in sublingual and 14/67 hours in vaginal). There was no significant difference in the success rate at 24 and 48 hours and in side effects. The preference for the sublingual route of administration was higher.Both vaginal and sublingual misoprostol are effective for medical abortion in second trimester termination. Conclusion: But it appears from shorter induction interval in sublingual and higher acceptability that sublingual route is a better choice.